2014
DOI: 10.1097/mcc.0000000000000123
|View full text |Cite
|
Sign up to set email alerts
|

Chronic obstructive pulmonary disease and the risk for ventilator-associated pneumonia

Abstract: COPD is a risk factor for VAP. Future studies should focus on specific preventive measures in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 58 publications
0
27
0
2
Order By: Relevance
“…Patients with severe ARF are usually managed with intubation and invasive mechanical ventilation (MV), but their clinical course is frequently complicated by ventilator associated pneumonia (VAP) [2]. The risk of VAP is particularly high in patients with malignancies, immunocompromise and chronic obstructive pulmonary disease (COPD) [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with severe ARF are usually managed with intubation and invasive mechanical ventilation (MV), but their clinical course is frequently complicated by ventilator associated pneumonia (VAP) [2]. The risk of VAP is particularly high in patients with malignancies, immunocompromise and chronic obstructive pulmonary disease (COPD) [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…8 The Centers for Disease Control and Prevention defines the criteria for developing VAP as a patient who is on mechanical ventilation for more than 2 calendar days with the day of ventilator placement being day 1 and the ventilator being in place on the date or the day before. 6 According to a cohort study of mechanically ventilated patients conducted in Austria, 10% of critically ill patients received mechanical ventilation because of an acute exacerbation of COPD in the year 1998, and 6% in 2010.…”
Section: Epidemiologymentioning
confidence: 99%
“…8 Makris et al 3 defined multidrug-resistant bacteria in VAP as methicillin-resistant Staphylococcus aureus, ceftazidime-or imipenem-resistant P aeruginosa, Acinetobacter baumannii, Stenotrophomonas maltophilia, and extendedspectrum "-lactamaseYproducing gram-negative bacilli. One of the largest studies on VAP in COPD patients found that P aeruginosa is responsible for 31% of VAP episodes, trailed by A baumannii at 19% and S aureus reaching 13%.…”
Section: Microbiologymentioning
confidence: 99%
See 2 more Smart Citations